Foreign Direct Investment: Does it Increase Economic Growth? - Suyanto Suyanto (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2023)
Economic growth is one indicator of development. Factors that are thought to be capable of influencing economic growth include the human development index, income, poverty, investment, and unemployment. So it needs to be analyzed to achieve sustainable development. This study aims to analyze the effect of human development index, income, poverty, investment, and unemployment on economic growth. The research method used is descriptive quantitative with panel data regression analysis. The data consists of six provinces on the island of Java starting from 2010-2021. The results of the study show that the development, income and unemployment indices have a negative and significant effect on economic growth, while the poverty and investment variables do not have a significant effect on economic growth. The government must be able to allocate an efficient budget that has a direct impact on economic growth both in the long term and in the short term. For the government to be able to focus more on policies on human development and expanding employment opportunities to be able to overcome economic growth in Java.